All-solid-state lithium ion battery and preparation method thereof

By introducing an interface modification layer into an all-solid-state lithium-ion battery, the interface impedance problem between the sulfide electrolyte layer and the negative electrode is solved, the formation of lithium dendrites is suppressed, and the rate performance and cycle stability of the battery are improved.

CN119340453AInactive Publication Date: 2025-01-21HEFEI GUOXUAN HIGH TECH POWER ENERGY

Patent Information

Application Number
CN202411598313.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When using sulfide solid electrolytes, existing all-solid lithium-ion batteries have huge interfacial impedance and lithium dendrites, resulting in poor battery rate performance and poor cycle performance.

Method used

An interface modification layer is introduced between the sulfide electrolyte layer and the negative electrode. The interface modification layer is composed of an ion transfer medium and an electron transfer medium. The ion transfer medium is selected from lithium-containing oxides, non-lithium metals and non-lithium metal oxides. The electron transfer medium Selected from carbon materials with a resistivity of 1×10-5 to 2×10-5Ω/cm.

Benefits of technology

Through the use of the interface modification layer, the nucleation barrier of metallic lithium can be reduced, the formation of lithium dendrites can be inhibited, the safety and cycle stability of the battery can be improved, the transmission efficiency of lithium ions and electrons can be improved, and the rate performance of the battery can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340453A_ABST
    Figure CN119340453A_ABST
Patent Text Reader

Abstract

The invention provides an all-solid-state lithium ion battery and a preparation method thereof. The all-solid-state lithium ion battery comprises a positive electrode, a sulfide electrolyte layer, an interface modification layer and a negative electrode which are sequentially stacked, the material of the interface modification layer comprises an ion transfer medium and an electron transfer medium, the ion transfer medium is selected from one or more of lithium-containing oxide, non-lithium metal and non-lithium metal oxide, and the electron transfer medium is selected from one or more of lithium-containing oxide, non-lithium metal and non-lithium metal oxide. And the electron transfer medium is selected from carbon materials with resistivity of 1 * 10 <-5 >-2 * 10 <-5 > omega / cm. The interface modification layer can enable passing lithium ions to be re-distributed and distributed more uniformly, and can reduce the nucleation barrier of metal lithium, so that the metal lithium can be uniformly deposited on the surface of the negative electrode, the formation of lithium dendrites can be inhibited, and the safety and cycling stability of the all-solid-state lithium ion battery can be further improved; and meanwhile, the transmission efficiency of lithium ions and electrons can be improved, so that the electrochemical performance of the all-solid-state lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of all-solid-state lithium-ion battery preparation, and in particular to an all-solid-state lithium-ion battery and a preparation method thereof. Background Art

[0002] With the popularity of electric vehicles, lithium-ion battery technology has developed by leaps and bounds. However, the energy density that can be achieved by graphite anodes in traditional lithium batteries is limited, and the use of metal lithium anodes is considered to be the ultimate solution to improve the energy density of lithium batteries. However, when using metal lithium anodes, there are problems such as uneven lithium stripping / deposition and the formation of lithium dendrites during battery cycling. Lithium dendrites may even penetrate the diaphragm, causing battery short circuits and serious safety problems. Solid-state lithium batteries are expected to inhibit the growth of lithium dendrites, increase battery energy density, and improve battery safety. Among the many types of solid electrolytes, sulfide solid electrolytes have been widely studied because of their high ionic conductivity comparable to organic electrolytes and good compatibility with commercial cathode materials.

[0003] However, even when using sulfide solid electrolytes, there is still a huge interface impedance of solid-solid contact and grain boundary impedance of sulfide grains and active materials, which requires a large external pressure to be applied when using sulfide all-solid batteries. The pressurized tooling makes it difficult to commercialize solid-state batteries. At the same time, the sulfide electrolyte is not stable enough when in contact with the metal lithium anode. A passivation layer with high resistance caused by chemical and electrochemical side reactions will form at the contact interface. In addition, due to the solid-solid contact at the interface, the pores present will interfere with the transmission of lithium ions and accelerate the formation of lithium dendrites, which severely limits the practical application of sulfide solid-state batteries. Therefore, there is an urgent need to find an innovative solution to overcome the challenges of using metal lithium anodes in sulfide solid-state batteries to ensure the long life, high performance and safety of the battery.

[0004] In the prior art, an intermediate layer is usually introduced between the metal lithium negative electrode and the sulfide solid electrolyte to improve the interface problem. This intermediate layer can be an inorganic solid electrolyte layer or an organic polymer electrolyte layer. As in the existing document (publication number CN117352856A), the patent claims that a thin layer of LiPON inorganic solid electrolyte is deposited by magnetron sputtering on one side of the sulfide electrolyte to the metal lithium, and then the molten metal lithium is dripped. This design is expected to improve the stability of the metal lithium negative electrode interface, but the problem with this method is that it is not conducive to large-scale production, and the expensive magnetron sputtering method is adopted. In comparison, the organic polymer intermediate layer has the possibility of large-scale production due to its simpler preparation and processing technology. As in the existing document (publication number CN114242958A), the patent claims that a gel-like ether polymer is coated on the surface of the metal lithium to obtain a metal lithium negative electrode with an interface layer modified, and assembled into a solid-state battery with a sulfide electrolyte. This design is expected to reduce the internal resistance of the solid-state battery and extend the life of the solid-state battery. However, the problem with this method is that the thickness of the intermediate layer cannot be effectively controlled. In addition, due to the high viscosity of gel-like ether polymers, the coating process may also have problems such as unevenness.

[0005] On this basis, researching and developing an interface modification layer that can significantly reduce the internal resistance of all-solid-state lithium-ion batteries and inhibit lithium dendrites is of great significance for improving their rate performance and cycle performance. Summary of the invention

[0006] The main purpose of the present invention is to provide an all-solid-state lithium ion battery and a preparation method thereof, so as to solve the problems in the prior art that the interface impedance between the electrolyte layer and the negative electrode is large, resulting in poor rate performance of the all-solid-state lithium ion battery, and when metallic lithium is used as the negative electrode, lithium dendrites are easily formed during the battery cycle, resulting in the all-solid-state lithium ion battery being prone to short circuit and having poor cycle performance.

[0007] In order to achieve the above-mentioned object, the present invention provides an all-solid-state lithium-ion battery, which comprises a positive electrode, a sulfide electrolyte layer, an interface modification layer and a negative electrode stacked in sequence, wherein the material of the interface modification layer comprises an ion transfer medium and an electron transfer medium, the ion transfer medium is selected from one or more of the group consisting of lithium oxide, non-lithium metal and non-lithium metal oxide, and the electron transfer medium is selected from a resistivity of 1×10 -5 ~2×10 -5 Ω / cm carbon material.

[0008] The traditional all-solid-state lithium-ion battery has a laminated structure in which a positive electrode, a sulfide electrolyte layer and a negative electrode are stacked in sequence. During the charge and discharge process, lithium ions are reduced and deposited on the surface of the negative electrode, and lithium dendrites are easily formed during the deposition process, causing the battery to short-circuit. The all-solid-state lithium-ion battery provided by the present application also includes an interface modification layer arranged between the sulfide electrolyte layer and the negative electrode, and the interface modification layer includes an ion transfer medium and an electron transfer medium, which can redistribute the lithium ions passing through and distribute them more uniformly, and can reduce the nucleation barrier of metallic lithium, so that metallic lithium can be uniformly deposited on the negative electrode surface, and the formation of lithium dendrites can be suppressed, thereby improving the safety and cycle stability of the all-solid-state lithium-ion battery. Moreover, the above-mentioned interface modification layer includes an ion transfer medium and an electron transfer medium, which can simultaneously improve the transmission efficiency of lithium ions and electrons, thereby improving the electrochemical properties such as the rate performance of the all-solid-state lithium-ion battery.

[0009] Compared with other types, using the above-mentioned carbon material with specific resistivity as an electron transfer medium is beneficial to improving the electron transfer efficiency, thereby helping to improve the electrochemical properties such as the rate performance of the all-solid-state lithium-ion battery.

[0010] Furthermore, the lithium potential of the lithium-containing oxide is ≥1 V to lithium, and the volume expansion rate after combining with lithium is ≤5%.

[0011] Compared with other types, the use of the above-mentioned lithium-containing oxide as an ion transfer medium is beneficial to improving the lithium ion transmission efficiency while reducing volume expansion, which is beneficial to improving the structural stability of the all-solid-state lithium-ion battery, thereby improving its cycle performance and safety.

[0012] Furthermore, the potential of the non-lithium metal and the non-lithium metal oxide to lithium is ≥ 0.3 V, and the binding energy of lithium is ≤ 0.5 eV.

[0013] Compared with other types, using the above lithium-containing oxide as an ion transfer medium is beneficial to improving the lithium ion transmission efficiency, thereby helping to improve the rate performance of all-solid-state lithium-ion batteries.

[0014] Furthermore, the weight ratio of the ion transfer medium to the electron transfer medium is 1:(2-4).

[0015] The weight ratio of the ion transfer medium to the electron transfer medium includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the transmission efficiency of lithium ions and electrons, and is also beneficial to inhibiting the formation of lithium dendrites.

[0016] Furthermore, the lithium-containing oxide is selected from one or more of the group consisting of lithium titanate, lithium vanadium titanate and lithium yttrium titanate.

[0017] Compared with other types, the use of the above-mentioned lithium-containing oxide as an ion transfer medium is beneficial to improving the lithium ion transmission efficiency while reducing volume expansion, which is beneficial to improving the structural stability of the all-solid-state lithium-ion battery, thereby improving its cycle performance and safety.

[0018] Further, the non-lithium metal is selected from silver and / or gold.

[0019] Compared with other types, the use of the above-mentioned non-lithium metals as ion transfer media is beneficial to improving the lithium ion transmission efficiency while reducing volume expansion, which is beneficial to improving the structural stability of all-solid-state lithium-ion batteries, thereby improving their cycle performance.

[0020] Further, the non-lithium metal oxide is selected from one or more of the group consisting of zinc oxide, titanium dioxide and magnesium oxide.

[0021] Non-lithium metal oxides include but are not limited to the above range. Limiting them within the above range is beneficial to reducing volume expansion while improving lithium ion transmission efficiency, which is beneficial to improving the structural stability of all-solid-state lithium-ion batteries, thereby improving their cycle performance.

[0022] Furthermore, the thickness of the interface modification layer is 3 to 15 μm, preferably 5 to 10 μm.

[0023] The thickness of the interface modification layer includes but is not limited to the above range. Limiting it within the above range is conducive to better exerting the role of the interface modification layer, and is conducive to improving the uniformity of lithium ion distribution, thereby helping to inhibit the formation of lithium dendrites, thereby improving the cycle performance of the all-solid-state lithium-ion battery; at the same time, it is also conducive to improving the transmission efficiency of lithium ions and electrons, thereby improving the rate performance of the all-solid-state lithium-ion battery.

[0024] Furthermore, the thickness of the sulfide electrolyte layer is 20 to 100 μm.

[0025] The thickness of the sulfide electrolyte layer includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the lithium ion transmission efficiency, thereby improving the rate performance of the all-solid-state lithium-ion battery.

[0026] Further, the positive electrode includes a positive electrode current collector layer and a positive electrode active material layer, and the positive electrode active material layer is disposed between the positive electrode current collector layer and the sulfide electrolyte layer.

[0027] Furthermore, the thickness of the positive electrode active material layer is 150 to 300 μm.

[0028] The thickness of the positive electrode active material layer includes but is not limited to the above range. Limiting the thickness within the above range is conducive to better exerting the electrochemical properties of the positive electrode active material, such as the energy density.

[0029] Furthermore, the material of the positive electrode current collector layer is selected from aluminum.

[0030] Further, the material of the positive electrode active material layer is selected from one or more of the group consisting of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate and lithium-rich manganese-based materials.

[0031] Furthermore, the material of the sulfide electrolyte layer is selected from Li3PS4, Li 10 GeP2S 12 、Li7P3S 11 and one or more of the group consisting of Li6PS5X type electrolytes.

[0032] The materials of the sulfide electrolyte layer include but are not limited to the above-mentioned types. The use of the above-mentioned types is beneficial to improving the transmission efficiency of lithium ions, thereby improving the comprehensive electrochemical properties of the all-solid-state lithium-ion battery, such as the rate performance.

[0033] Furthermore, the material of the negative electrode is selected from metallic lithium and / or silicon-carbon composite lithium.

[0034] Compared with other types, the use of the above-mentioned types of negative electrode materials is beneficial to improving the electron transfer efficiency, thereby improving the comprehensive electrochemical properties of all-solid-state lithium-ion batteries such as rate performance; it is also beneficial to improving its cycle stability.

[0035] In order to achieve the above-mentioned purpose, another aspect of the present invention also provides a method for preparing the above-mentioned all-solid-state lithium-ion battery provided in the present application, and the preparation method comprises: step S1, mixing an ion transfer medium, an electron transfer medium, a first solvent and a first binder to obtain a slurry; coating the slurry on one side surface of the negative electrode, and obtaining a laminated structure containing an interface modification layer after drying; step S2, sequentially preparing a sulfide electrolyte layer and a positive electrode on one side surface close to the interface modification layer in the laminated structure to obtain an all-solid-state lithium-ion battery.

[0036] In the present application, the above-mentioned interface modification layer can be prepared by wet coating. Specifically, an ion transfer medium, an electron transfer medium, a first solvent and a first binder are mixed to obtain a slurry; the slurry is coated on one surface of the negative electrode, and after drying, a laminated structure containing the interface modification layer is obtained.

[0037] The traditional all-solid-state lithium-ion battery has a laminated structure in which a positive electrode, a sulfide electrolyte layer and a negative electrode are stacked in sequence. During the charge and discharge process, lithium ions are reduced and deposited on the surface of the negative electrode, and lithium dendrites are easily formed during the deposition process, causing the battery to short-circuit. The all-solid-state lithium-ion battery provided by the present application also includes an interface modification layer arranged between the sulfide electrolyte layer and the negative electrode, and the interface modification layer includes an ion transfer medium and an electron transfer medium, which can redistribute the lithium ions passing through and distribute them more uniformly, and can reduce the nucleation barrier of metallic lithium, so that metallic lithium can be uniformly deposited on the negative electrode surface, and the formation of lithium dendrites can be suppressed, thereby improving the safety and cycle stability of the all-solid-state lithium-ion battery. Moreover, the above-mentioned interface modification layer includes an ion transfer medium and an electron transfer medium, which can simultaneously improve the transmission efficiency of lithium ions and electrons, thereby improving the electrochemical properties such as the rate performance of the all-solid-state lithium-ion battery.

[0038] The method has a simple process flow and is easy to control parameters such as the thickness and density of the interface modification layer, thereby facilitating obtaining a relatively uniform interface modification layer.

[0039] Furthermore, the weight ratio of the sum of the weights of the ion transfer medium and the electron transfer medium to the first binder is (3-7):100.

[0040] The weight ratio of the sum of the weights of the ion transfer medium and the electron transfer medium to the first binder includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the transmission efficiency of lithium ions and electrons, and is also beneficial to inhibiting the formation of lithium dendrites.

[0041] Further, the first binder is selected from one or more of the group consisting of polyvinylidene fluoride, polychloroprene, polyvinylidene fluoride-hexafluoropropylene and styrene-butadiene rubber.

[0042] Compared with other types, the use of the above-mentioned first binder is beneficial to improving the processability of the slurry, thereby improving the adhesion of the ion transfer medium and the electron transfer medium, and further improving the bonding force between the interface modification layer and the negative electrode, which is beneficial to the role of the interface modification layer.

[0043] Further, the first solvent is selected from one or more of the group consisting of NMP, DMF and cyclohexanone.

[0044] Compared with other types, the use of the above-mentioned first solvent is beneficial to improving the processability of the slurry, and is also beneficial to improving the dispersibility of the ion transfer medium and the electron transfer medium in the first solvent.

[0045] Furthermore, the solid content of the slurry is 5 to 20 wt %.

[0046] The solid content of the slurry includes but is not limited to the above range. Limiting the solid content of the slurry within the above range is beneficial to further improve the processability of the slurry.

[0047] Furthermore, the average particle size of the ion transport medium is 30 to 200 nm, preferably 50 to 80 nm.

[0048] The average particle size of the ion transfer medium includes but is not limited to the above range. Limiting it within the above range is beneficial to shortening the lithium ion transmission path, thereby facilitating improving the rate performance of the all-solid-state lithium ion battery.

[0049] Furthermore, the electron transfer medium is in a granular or tubular shape, and the average particle diameter or average tube diameter of the electron transfer medium is 20 to 80 nm, preferably 30 to 60 nm.

[0050] The average particle size of the electron transfer medium includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the interface contact between the sulfide electrolyte layer and the negative electrode, and at the same time is beneficial to improving the conductivity, thereby helping to improve the cycle performance and rate performance of the all-solid-state lithium-ion battery.

[0051] Furthermore, in step S1, the drying temperature is 80-150° C. and the drying time is 12-24 hours.

[0052] The drying temperature and time include but are not limited to the above ranges. Limiting them within the above ranges is beneficial to inhibiting the damage to the interface modification layer caused by excessively high temperatures and inhibiting the redispersion of the first binder in the two media caused by excessively low temperatures, which is beneficial to better exerting the role of the interface modification layer and further improving the cycle performance and rate performance of all-solid-state lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0054] Figure 1 A schematic diagram of the stacked structure of an all-solid-state lithium-ion battery in a preferred embodiment of the present application is shown;

[0055] Figure 2 A schematic diagram of the stacked structure of the all-solid-state lithium-ion battery provided in Example 1 is shown;

[0056] Figure 3 A schematic diagram of the stacked structure of the all-solid-state lithium-ion battery provided in Comparative Example 1 is shown.

[0057] The above drawings include the following reference numerals:

[0058] 10. positive electrode; 20. sulfide electrolyte layer; 30. interface modification layer; 40. negative electrode; 11. positive electrode current collector layer; 12. positive electrode active material layer. DETAILED DESCRIPTION

[0059] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0060] As described in the background technology, the existing all-solid-state lithium-ion battery has a large interface impedance between the electrolyte layer and the negative electrode, resulting in poor rate performance of the all-solid-state lithium-ion battery, and when metallic lithium is used as the negative electrode, lithium dendrites are easily formed during the battery cycle, resulting in the all-solid-state lithium-ion battery being prone to short circuit and poor cycle performance. In order to solve the above technical problems, the first aspect of the present application provides an all-solid-state lithium-ion battery, such as Figure 1 As shown, the all-solid-state lithium-ion battery comprises a positive electrode 10, a sulfide electrolyte layer 20, an interface modification layer 30 and a negative electrode 40 which are stacked in sequence, wherein the material of the interface modification layer 30 comprises an ion transfer medium and an electron transfer medium, the ion transfer medium is selected from one or more of the group consisting of lithium oxide, non-lithium metal and non-lithium metal oxide, and the electron transfer medium is selected from a group consisting of a resistivity of 1×10 -5 ~2×10 -5 Ω / cm carbon material.

[0061] The conventional all-solid-state lithium-ion battery has a laminated structure in which a positive electrode 10, a sulfide electrolyte layer 20 and a negative electrode 40 are stacked in sequence. During the charge and discharge process, the lithium ions are reduced and deposited on the surface of the negative electrode 40, and lithium dendrites are easily formed during the deposition process, causing the battery to short-circuit. The all-solid-state lithium-ion battery provided by the present application also includes an interface modification layer 30 arranged between the sulfide electrolyte layer 20 and the negative electrode 40, and the interface modification layer 30 includes an ion transfer medium and an electron transfer medium, which can redistribute the lithium ions passing through and distribute them more uniformly, and can reduce the nucleation barrier of metallic lithium, so that metallic lithium can be uniformly deposited on the surface of the negative electrode 40, and the formation of lithium dendrites can be suppressed, thereby improving the safety and cycle stability of the all-solid-state lithium-ion battery. Moreover, the above-mentioned interface modification layer 30 includes an ion transfer medium and an electron transfer medium, which can simultaneously improve the transmission efficiency of lithium ions and electrons, thereby improving the electrochemical properties such as the rate performance of the all-solid-state lithium-ion battery.

[0062] Compared with other types, using the above-mentioned carbon material with specific resistivity as an electron transfer medium is beneficial to improving the electron transfer efficiency, thereby helping to improve the electrochemical properties such as the rate performance of the all-solid-state lithium-ion battery.

[0063] In a preferred embodiment, the lithium-containing oxide has a potential of ≥1 V to lithium and a volume expansion rate of ≤5% after combining with lithium. Compared with other types, the use of the lithium-containing oxide as an ion transfer medium is beneficial to improving the lithium ion transmission efficiency while reducing volume expansion, and is beneficial to improving the structural stability of the all-solid-state lithium-ion battery, thereby improving its cycle performance and safety.

[0064] In a preferred embodiment, the potential of the non-lithium metal and the non-lithium metal oxide to lithium is ≥0.3V, and the binding energy of lithium is ≤0.5eV. Compared with other types, the use of the above lithium-containing oxide as an ion transfer medium is conducive to improving the lithium ion transfer efficiency, thereby improving the rate performance of the all-solid-state lithium-ion battery.

[0065] In this application, the lithium potential refers to the potential relative to the electric pair Li / Li + The electrode potential.

[0066] In order to further improve the transmission efficiency of lithium ions and electrons and further inhibit the formation of lithium dendrites, preferably, the weight ratio of the ion transfer medium to the electron transfer medium is 1:(2-4).

[0067] In a preferred embodiment, the lithium-containing oxide includes but is not limited to one or more of the group consisting of lithium titanate, lithium vanadium titanate and lithium yttrium titanate. Compared with other types, the use of the above lithium-containing oxide as an ion transfer medium is beneficial to improving the lithium ion transmission efficiency while reducing volume expansion, and is beneficial to improving the structural stability of the all-solid-state lithium-ion battery, thereby improving its cycle performance and safety.

[0068] In a preferred embodiment, the non-lithium metal includes but is not limited to silver and / or gold. Compared with other types, the use of the non-lithium metal as an ion transfer medium is beneficial to reducing volume expansion while improving lithium ion transmission efficiency, and is beneficial to improving the structural stability of the all-solid-state lithium-ion battery, thereby improving its cycle performance.

[0069] In a preferred embodiment, the non-lithium metal oxide includes but is not limited to one or more of the group consisting of zinc oxide, titanium dioxide and magnesium oxide. The non-lithium metal oxide includes but is not limited to the above range, and limiting it within the above range is beneficial to reducing volume expansion while improving lithium ion transmission efficiency, and is beneficial to improving the structural stability of the all-solid-state lithium-ion battery, thereby improving its cycle performance.

[0070] In a preferred embodiment, the thickness of the interface modification layer 30 is 3 to 15 μm. The thickness of the interface modification layer 30 includes but is not limited to the above range. Limiting it within the above range is beneficial to better play the role of the interface modification layer 30, beneficial to improving the uniformity of lithium ion distribution, thus beneficial to inhibiting the formation of lithium dendrites, and further improving the cycle performance of the all-solid-state lithium ion battery; at the same time, it is also beneficial to improving the transmission efficiency of lithium ions and electrons, and further improving the rate performance of the all-solid-state lithium ion battery.

[0071] In order to further play the role of the interface modification layer 30 and thus further improve the cycle performance and rate performance of the all-solid-state lithium ion battery, preferably, the thickness of the interface modification layer 30 is 5 to 10 μm.

[0072] In a preferred embodiment, the thickness of the sulfide electrolyte layer 20 is 20 to 100 μm. The thickness of the sulfide electrolyte layer 20 includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the lithium ion transmission efficiency, and thus beneficial to improving the rate performance of the all-solid-state lithium ion battery.

[0073] In a preferred embodiment, as Figure 2 shown, the positive electrode 10 includes a positive electrode current collector layer 11 and a positive electrode active material layer 12, and the positive electrode active material layer 12 is disposed between the positive electrode current collector layer 11 and the sulfide electrolyte layer 20. The setting of the positive electrode current collector layer 11 is beneficial to improving the conductivity of the all-solid-state lithium ion battery and can provide mechanical strength. At the same time, the setting of the positive electrode active material layer 12 can provide a lithium ion source for the all-solid-state lithium ion battery, and thus can provide electrochemical properties such as energy density.

[0074] In order to better play the electrochemical properties such as the energy density of the positive electrode active material, preferably, the thickness of the positive electrode active material layer 12 is 150 to 300 μm.

[0075] The present application does not particularly limit the material of the positive electrode current collector layer 11, and it is sufficient that it can have good conductivity and mechanical properties. In a preferred embodiment, the material of the positive electrode current collector layer 11 includes but is not limited to aluminum.

[0076] The present application does not particularly limit the positive electrode active material, and it is sufficient that it can provide a high energy density. In a preferred embodiment, the material of the positive electrode active material layer 12 includes but is not limited to one or more of the group consisting of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, and lithium-rich manganese-based materials. Among them, the lithium-rich manganese-based material refers to the general formula xLi2MnO3·(1-x)LiMO2, where 0 < x < 1, and M = Ni, Co, Mn and other transition metal elements and their combinations.

[0077] In a preferred embodiment, the material of the sulfide electrolyte layer 20 includes but is not limited to Li3PS4, Li 10 GeP2S 12 、Li7P3S 11 The materials of the sulfide electrolyte layer 20 include but are not limited to the above-mentioned types, and the use of the above-mentioned types is conducive to improving the transmission efficiency of lithium ions, thereby improving the comprehensive electrochemical properties of the all-solid-state lithium-ion battery, such as the rate performance.

[0078] In a preferred embodiment, the material of the negative electrode 40 includes but is not limited to metallic lithium and / or silicon-carbon composite lithium. Compared with other types, the use of the negative electrode 40 materials of the above types is conducive to improving the electron transmission efficiency, thereby improving the comprehensive electrochemical performance of the all-solid-state lithium-ion battery such as the rate performance; and also helps to improve its cycle stability.

[0079] The second aspect of the present application provides a method for preparing the above-mentioned all-solid-state lithium-ion battery provided by the present application, and the preparation method comprises: step S1, mixing an ion transfer medium, an electron transfer medium, a first solvent and a first binder to obtain a slurry; coating the slurry on one side surface of the negative electrode 40, and obtaining a laminated structure containing an interface modification layer 30 after drying; step S2, sequentially preparing a sulfide electrolyte layer 20 and a positive electrode 10 on one side surface close to the interface modification layer 30 in the laminated structure to obtain an all-solid-state lithium-ion battery.

[0080] In the present application, the interface modification layer 30 can be prepared by wet coating. Specifically, an ion transfer medium, an electron transfer medium, a first solvent and a first binder are mixed to obtain a slurry; the slurry is coated on one side surface of the negative electrode 40, and after drying, a laminated structure containing the interface modification layer 30 is obtained.

[0081] The conventional all-solid-state lithium-ion battery has a laminated structure in which a positive electrode 10, a sulfide electrolyte layer 20 and a negative electrode 40 are stacked in sequence. During the charge and discharge process, the lithium ions are reduced and deposited on the surface of the negative electrode 40, and lithium dendrites are easily formed during the deposition process, causing the battery to short-circuit. The all-solid-state lithium-ion battery provided by the present application also includes an interface modification layer 30 arranged between the sulfide electrolyte layer 20 and the negative electrode 40, and the interface modification layer 30 includes an ion transfer medium and an electron transfer medium, which can redistribute the lithium ions passing through and distribute them more uniformly, and can reduce the nucleation barrier of metallic lithium, so that metallic lithium can be uniformly deposited on the surface of the negative electrode 40, and the formation of lithium dendrites can be suppressed, thereby improving the safety and cycle stability of the all-solid-state lithium-ion battery. Moreover, the above-mentioned interface modification layer 30 includes an ion transfer medium and an electron transfer medium, which can simultaneously improve the transmission efficiency of lithium ions and electrons, thereby improving the electrochemical properties such as the rate performance of the all-solid-state lithium-ion battery.

[0082] The above method has a simple process flow and is easy to control parameters such as the thickness and density of the interface modification layer 30 , thereby facilitating obtaining a relatively uniform interface modification layer 30 .

[0083] In a preferred embodiment, the preparation process of the sulfide electrolyte layer 20 includes: mixing the sulfide electrolyte, the second binder, and the second solvent by a ball mill disperser or a mechanical stirrer, preparing an electrolyte slurry, coating the slurry, and drying to obtain the sulfide electrolyte layer 20.

[0084] In order to improve the electrochemical performance of all-solid-state lithium-ion batteries, preferably, sulfide electrolytes include but are not limited to Li3PS4, Li 10 GeP2S 12 、Li7P3S 11 and one or more of the group consisting of Li6PS5X type electrolytes.

[0085] In a preferred embodiment, the preparation process of the positive electrode 10 includes: mixing the positive electrode material, sulfide electrolyte, conductive agent, third binder, and third solvent by a ball mill disperser or a mechanical stirrer, preparing a positive electrode slurry, coating the mixture, and drying the mixture to obtain the positive electrode 10.

[0086] In order to further improve the transmission efficiency of lithium ions and electrons and further inhibit the formation of lithium dendrites, preferably, the weight ratio of the sum of the weights of the ion transfer medium and the electron transfer medium to the first binder is (3-7):100.

[0087] In a preferred embodiment, the first binder includes, but is not limited to, one or more of the group consisting of polyvinylidene fluoride, polychloroprene, polyvinylidene fluoride-hexafluoropropylene and styrene-butadiene rubber. Compared with other types, the use of the above-mentioned first binder is conducive to improving the processability of the slurry, thereby improving the adhesion of the ion transfer medium and the electron transfer medium, thereby improving the bonding force between the interface modification layer 30 and the negative electrode 40, which is conducive to exerting the role of the interface modification layer 30.

[0088] In order to further improve the processability of the slurry and to further improve the bonding strength between the interface modification layer 30 and the negative electrode 40, preferably, the weight average molecular weight of polyvinylidene fluoride is 600,000 to 1.2 million, the weight average molecular weight of polychloroprene is 200,000 to 800,000, the weight average molecular weight of polyvinylidene fluoride-hexafluoropropylene is 100,000 to 600,000, and the weight average molecular weight of styrene-butadiene rubber is 200,000 to 800,000.

[0089] In order to further improve the processability of the slurry used to prepare the interface modification layer 30 and improve the dispersibility of the ion transfer medium and the electron transfer medium in the first solvent, in a preferred embodiment, the first solvent includes but is not limited to one or more of the group consisting of NMP, DMF and cyclohexanone.

[0090] In order to further improve the processability of the slurry used to prepare the interface modification layer 30, in a preferred embodiment, the solid content of the slurry is 5-20 wt%.

[0091] In a preferred embodiment, the average particle size of the ion transport medium is 30 to 200 nm, preferably 50 to 80 nm. The average particle size of the ion transport medium includes but is not limited to the above range, and limiting it within the above range is conducive to shortening the lithium ion transmission path, thereby facilitating improving the rate performance of the all-solid-state lithium ion battery.

[0092] In a preferred embodiment, the electron transfer medium is granular or tubular, and the average particle size or average tube size of the electron transfer medium is 20 to 80 nm, preferably 30 to 60 nm. The average particle size of the electron transfer medium includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the interface contact between the sulfide electrolyte layer 20 and the negative electrode 40, and is also beneficial to improving the conductivity, thereby improving the cycle performance and rate performance of the all-solid-state lithium-ion battery.

[0093] In a preferred embodiment, the drying temperature is 80-150°C and the drying time is 12-24 hours. The drying temperature and time include but are not limited to the above ranges. Limiting them within the above ranges is conducive to suppressing the damage to the interface modification layer 30 by excessively high temperatures and suppressing the redispersion of the first binder in the two media by excessively low temperatures, which is conducive to better exerting the role of the interface modification layer 30 and further improving the cycle performance and rate performance of the all-solid-state lithium-ion battery.

[0094] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0095] Example 1

[0096] A method for preparing an all-solid-state lithium-ion battery, comprising:

[0097] (1) Preparation of interface modification layer 30:

[0098] 1 part by weight of lithium titanate with an average particle size of 50 nm, 3 parts by weight of acetylene black with an average particle size of 40 nm, 92 parts by weight of N-methylpyrrolidone and 4 parts by weight of vinylidene fluoride are mixed to obtain a slurry with a solid content of 8 wt %; the slurry is coated on one side of a lithium foil (negative electrode 40) with a thickness of 20 μm, and dried at 120° C. for 12 h to obtain a laminated structure containing an interface modification layer 30; wherein the lithium titanate has a potential of 1.5 V to lithium, a volume expansion rate of 1% after combining with lithium, and a resistivity of 10 -5 Ω / cm;

[0099] (2) Preparation of sulfide electrolyte layer 20:

[0100] The Li6PS5Cl electrolyte, nitrile rubber and xylene in a weight ratio of 97:3:80 were mixed by a ball mill disperser to prepare a slurry with a solid content of 55.6wt%, and then coated and dried to obtain a sulfide electrolyte layer, thereby obtaining a Li6PS5Cl electrolyte layer;

[0101] (3) Preparation of positive electrode active material layer 12:

[0102] Using nickel-cobalt-manganese ternary material NCM811 as the positive electrode active material, a positive electrode slurry containing the positive electrode active material is coated on one side of an aluminum foil (positive electrode current collector layer 11) having a thickness of 16 μm to obtain a laminated structure containing a positive electrode active material layer 12;

[0103] (4) Preparation of all-solid-state lithium-ion batteries:

[0104] The laminated structure containing the interface modification layer 30, the sulfide electrolyte layer 20 and the laminated structure containing the positive electrode active material layer 12 are stacked and pressed at a pressure of 500 kPa for 5 minutes to obtain an all-solid-state lithium-ion battery. Figure 2 As shown, the all-solid-state lithium-ion battery includes a positive electrode current collector layer 11, a positive electrode active material layer 12, a sulfide electrolyte layer 20, an interface modification layer 30 and a negative electrode 40 which are stacked in sequence, wherein the thickness of the positive electrode active material layer 12 is 200 μm, the thickness of the sulfide electrolyte layer 20 is 30 μm, and the thickness of the interface modification layer 30 is 8 μm.

[0105] Example 2

[0106] The difference from Example 1 is that in step (1), an equal amount of silver (average particle size of 60 nm) is used to replace lithium titanate as the ion transfer medium, and an equal amount of superconducting carbon black (average particle size of 30 nm) is used to replace acetylene carbon black as the electron transfer medium. The remaining steps are the same, wherein the potential of silver to lithium is 0.4 V, the binding energy with lithium is 0.3 eV, and the resistivity of superconducting carbon black is 2×10 -5 Ω / cm.

[0107] In the prepared all-solid-state lithium-ion battery, the thickness of the interface modification layer 30 is 12 μm.

[0108] Example 3

[0109] The difference from Example 1 is that the formula of the slurry in step (1) is different. The slurry includes: 0.5 parts by weight of lithium vanadium titanate with an average particle size of 40 nm, 0.5 parts by weight of zinc oxide with an average particle size of 80 nm, 2 parts by weight of Ketjen black with an average particle size of 40 μm, 0.5 parts by weight of carbon nanotubes with a diameter of 20 nm and a length of 0.5 μm, 92 parts by weight of N-methylpyrrolidone and 4 parts by weight of vinylidene fluoride, wherein the lithium vanadium titanate has a potential of 1.2 V to lithium and a volume expansion rate of 4% after combining with lithium, the potential of zinc oxide to lithium is 1.2 V and a binding energy with lithium is 0.4 eV, and the resistivity of Ketjen black is 10 -5 Ω / cm, the resistivity of carbon nanotubes is 10 -5 Ω / cm.

[0110] In the prepared all-solid-state lithium-ion battery, the thickness of the interface modification layer 30 is 15 μm.

[0111] Example 4

[0112] The difference from Example 1 is that the formula of the slurry in step (1) is different. The slurry comprises: 0.6 parts by weight of silver with an average particle size of 40 nm, 0.4 parts by weight of titanium dioxide with an average particle size of 30 nm, 2 parts by weight of Ketjen black with an average particle size of 30 μm, 1 part by weight of acetylene black with an average particle size of 30 μm, 92 parts by weight of N-methylpyrrolidone and 4 parts by weight of vinylidene fluoride, wherein the potential of silver to lithium is 0.4 V, and the binding energy with lithium is 0.3 eV, the potential of titanium dioxide to lithium is 1.5 V, and the binding energy with lithium is 0.4 eV, and the resistivity of Ketjen black is 10 -5 Ω / cm, the resistivity of acetylene black is 10 -5 Ω / cm.

[0113] In the prepared all-solid-state lithium-ion battery, the thickness of the interface modification layer 30 is 10 μm.

[0114] Example 5

[0115] The difference from Example 1 is that the formula of the slurry in step (1) is different. The slurry includes: 0.5 parts by weight of lithium yttrium titanate with an average particle size of 40 nm, 0.5 parts by weight of magnesium oxide with an average particle size of 30 nm, 2.5 parts by weight of Ketjen black with an average particle size of 40 μm, 92 parts by weight of N-methylpyrrolidone and 4 parts by weight of vinylidene fluoride, wherein the lithium potential of lithium yttrium titanate is 1.5 V, and the volume expansion rate after combining with lithium is 3%, the lithium potential of magnesium oxide is 1.4 V, and the binding energy with lithium is 0.4 eV, and the resistivity of Ketjen black is 10 -5 Ω / cm.

[0116] Example 6

[0117] The difference from Example 1 is that in step (1), the weight ratio of lithium titanate to acetylene black is 1:2.

[0118] Example 7

[0119] The difference from Example 1 is that in step (1), the weight ratio of lithium titanate to acetylene black is 1:4.

[0120] Example 8

[0121] The difference from Example 1 is that in step (1), the weight ratio of lithium titanate to acetylene black is 1:1.5.

[0122] Example 9

[0123] The difference from Example 1 is that the coating thickness is changed so that the thickness of the prepared interface modification layer 30 is 3 μm.

[0124] Example 10

[0125] The difference from Example 1 is that the coating thickness is changed so that the thickness of the prepared interface modification layer 30 is 15 μm.

[0126] Embodiment 11

[0127] The difference from Example 1 is that the coating thickness is changed so that the thickness of the prepared interface modification layer 30 is 1 μm.

[0128] Comparative Example 1

[0129] The difference from Example 1 is that step (1) is omitted, and the interface modification layer 30 is not prepared. The remaining steps are the same as those in Example 1. Figure 3 As shown, the prepared all-solid-state lithium-ion battery includes a positive electrode current collector layer 11, a positive electrode active material layer 12, a sulfide electrolyte layer 20 and a negative electrode 40 which are stacked in sequence.

[0130] Comparative Example 2

[0131] The difference from Example 1 is that acetylene black is not added in step (1).

[0132] Comparative Example 3

[0133] The difference from Example 1 is that lithium titanate is not added in step (1).

[0134] The all-solid-state lithium-ion batteries prepared in all the above embodiments and comparative examples of the present application were tested for rate performance and cycle performance. The rate performance test conditions were: 3MPa, 60°C, and the cycle performance test conditions were: 30°C, voltage range 2.5-4.25V, cycle 300 cycles, and measure the capacity retention rate. The test results are shown in Table 1. In Table 1, " / " indicates a short circuit.

[0135] Table 1

[0136]

[0137] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0138] The conventional all-solid-state lithium-ion battery has a laminated structure in which a positive electrode 10, a sulfide electrolyte layer 20 and a negative electrode 40 are stacked in sequence. During the charge and discharge process, the lithium ions are reduced and deposited on the surface of the negative electrode 40, and lithium dendrites are easily formed during the deposition process, causing the battery to short-circuit. The all-solid-state lithium-ion battery provided by the present application also includes an interface modification layer 30 arranged between the sulfide electrolyte layer 20 and the negative electrode 40, and the interface modification layer 30 includes an ion transfer medium and an electron transfer medium, which can redistribute the lithium ions passing through and distribute them more uniformly, and can reduce the nucleation barrier of metallic lithium, so that metallic lithium can be uniformly deposited on the surface of the negative electrode 40, and the formation of lithium dendrites can be suppressed, thereby improving the safety and cycle stability of the all-solid-state lithium-ion battery. Moreover, the above-mentioned interface modification layer 30 includes an ion transfer medium and an electron transfer medium, which can simultaneously improve the transmission efficiency of lithium ions and electrons, thereby improving the electrochemical properties such as the rate performance of the all-solid-state lithium-ion battery.

[0139] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0140] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises a positive electrode (10), a sulfide electrolyte layer (20), an interface modification layer (30) and a negative electrode (40) which are stacked in sequence, wherein the material of the interface modification layer (30) comprises an ion transfer medium and an electron transfer medium, wherein the ion transfer medium is selected from one or more of the group consisting of lithium oxides, non-lithium metals and non-lithium metal oxides, and the electron transfer medium is selected from a group consisting of a resistivity of 1×10 -5 ~2×10 -5 Ω / cm carbon material.

2. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The lithium oxide has a potential of ≥1V to lithium and a volume expansion rate of ≤5% after combining with lithium; Preferably, the non-lithium metal and the non-lithium metal oxide have a potential to lithium of ≥0.3 V, and a binding energy of lithium of ≤0.5 eV.

3. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The weight ratio of the ion transfer medium to the electron transfer medium is 1:(2-4).

4. The all-solid-state lithium-ion battery according to any one of claims 1 to 3, characterized in that: The lithium-containing oxide is selected from one or more of the group consisting of lithium titanate, lithium vanadium titanate and lithium yttrium titanate; Preferably, the non-lithium metal is selected from silver and / or gold; Preferably, the non-lithium metal oxide is selected from one or more of the group consisting of zinc oxide, titanium dioxide and magnesium oxide.

5. The all-solid-state lithium-ion battery according to claim 4, characterized in that: The thickness of the interface modification layer (30) is 3 to 15 μm, preferably 5 to 10 μm; Preferably, the thickness of the sulfide electrolyte layer (20) is 20 to 100 μm; Preferably, the positive electrode (10) comprises a positive electrode current collector layer (11) and a positive electrode active material layer (12), and the positive electrode active material layer (12) is arranged between the positive electrode current collector layer (11) and the sulfide electrolyte layer (20); More preferably, the thickness of the positive electrode active material layer (12) is 150 to 300 μm.

6. The all-solid-state lithium-ion battery according to claim 5, characterized in that: The material of the positive electrode current collector layer (11) is selected from aluminum; Preferably, the material of the positive electrode active material layer (12) is selected from one or more of the group consisting of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate and lithium-rich manganese-based materials; Preferably, the material of the sulfide electrolyte layer (20) is selected from Li3PS4, Li 10 GeP2S 12 、Li7P3S 11 One or more of the group consisting of and Li6PS5X type electrolyte; Preferably, the material of the negative electrode (40) is selected from metallic lithium and / or silicon-carbon composite lithium.

7. A method for preparing an all-solid-state lithium-ion battery according to any one of claims 1 to 6, characterized in that: The preparation method comprises: Step S1, mixing an ion transfer medium, an electron transfer medium, a first solvent and a first binder to obtain a slurry; coating the slurry on one side surface of the negative electrode (40), and obtaining a laminated structure containing an interface modification layer (30) after drying; Step S2, preparing a sulfide electrolyte layer (20) and a positive electrode (10) in sequence on a surface of one side of the laminate structure close to the interface modification layer (30) to obtain the all-solid-state lithium-ion battery.

8. The method for preparing an all-solid-state lithium-ion battery according to claim 7, characterized in that: The weight ratio of the sum of the weights of the ion transfer medium and the electron transfer medium to the first binder is (3-7):100; Preferably, the first binder is selected from one or more of the group consisting of polyvinylidene fluoride, polychloroprene, polyvinylidene fluoride-hexafluoropropylene and styrene-butadiene rubber; Preferably, the first solvent is selected from one or more of the group consisting of NMP, DMF and cyclohexanone; Preferably, the solid content of the slurry is 5-20 wt %.

9. The method for preparing an all-solid-state lithium-ion battery according to claim 7, characterized in that: The average particle size of the ion transport medium is 30 to 200 nm, preferably 50 to 80 nm; and / or, The electron transfer medium is in a granular or tubular shape, and the average particle diameter or average tube diameter of the electron transfer medium is 20 to 80 nm, preferably 30 to 60 nm.

10. The method for preparing an all-solid-state lithium-ion battery according to claim 7, characterized in that: In the step S1, the drying temperature is 80 to 150° C. and the drying time is 12 to 24 hours.

Citation Information

Patent Citations

  • Secondary battery and electric device

    CN115036555A

  • Alloy / carbon composite film for all-solid-state battery and preparation method of alloy / carbon composite film

    CN115763706A

  • Lithium metal negative electrode and preparation method and application thereof

    CN118676374A

  • KR20240063030A

Cited By

  • Lithium dendrite gradient shell neutralizer for solid-state battery and preparation method of lithium dendrite gradient shell neutralizer

    CN120895810A

  • Solid-state battery, preparation method and preparation equipment thereof, and electric equipment

    CN121905950A